Customer Service Mechanism Analysis At Bank Bjb Branch Of Tangerang City - Rachmat Gustiana; Mustofa Mustofa; Beby Pebri Nurjaman (Primanomics : Jurnal Ekonomi & Bisnis, 2021)
This study aims to explain the service mechanism at Bank BJB, Tangerang City Branch to its customers. The research objective was to explain the service level and customer satisfaction index value of the Bank BJB Branch of Tangerang City. The research method used is quantitative method with descriptive type. To measure the level of service used Likert scale analysis and to measure customer satisfaction used customer satisfaction index analysis. The results showed that the research hypothesis can be accepted, with a service level of 70.52%, which is above the critical value of acceptance of hi potesis by 60%. The results of the customer satisfaction index analysis resulted in a value of 89.53 which was included in the service class category A class which indicated that the services provided by the Bank BJB Branch of Tangerang City were very good.